(untitled) (Journal of Plant Disease Sciences, 2021)
Tomato (Solanum lycopersicum L.) is a most profitable vegetable crop; afflicted by a number of diseases, the most serious and destructive of which is early blight caused by Alternaria solani, which causes quantifiable losses. In present study evaluated in vitro efficacy of various fungicides at four different concentrations (250, 500, 750 and 1000 ppm). Among the fungicides tested, hexaconazole 4%+ zineb 68% inhibited 100% mycelium growth of the fungus at all concentration, while pyraclostrobin 133 G/L + epoxiconazole 50 G/L SE was the second best fungicide, inhibiting 89.62% mycelial growth at 250 ppm concentration and 100% mycelial growth at 500, 750, 1000 ppm concentrations, followed by kresoxim methyl 44.3 SC @0.044%. Difenoconazole 25 EC also recorded 100% mycelial inhibition at 750 and 1000 ppm concentrations, whereas the fungicide azoxystrobin 23 SC was found to be the least effective, with 38.82% inhibition at 250 ppm, 45.31% inhibition at 500 ppm, 54.45% inhibition at 750 ppm, and 70.34% inhibition at 1000 ppm concentrations, followed by carbendazim 50% WP.